Analysis of Student Learning Difficulties in the Material of Inheritance of Traits - Herinda Mardin; Aryati Abdul; Anita I. Sado (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to describe student learning difficulties in inheritance material in class XII SMA Negeri 1 Tapa. This type of research is descriptive quantitative. Data collection techniques used teacher activity sheets, student activity sheets, learning outcomes tests, questionnaires and interviews. The results of the study found: The results of learning implementation at meetings 1 and 2 with a value of 82, 81%, with a good category, at meetings 3 and 4 with a value of 78, 78 with a sufficient category. The results of student activity at meetings 1 to meeting 4 with a value of 54, 17, 51.17, 51.69, 53.39% with a less category. The results of student responses with aspects of physiology and psychology with a value of 69.58, 60.24% with a sufficient category and aspects of sociology with a value of 55.47% with a very sufficient percentage. The results of the analysis of learning outcomes tests with a value of 96% incomplete. In conclusion, there are many students who experience learning difficulties in terms of physiological, psychological, and sociological aspects.